KEWENANGAN OTORITA IKN DALAM PEMBUATAN PERJANJIAN INTERNASIONAL UNTUK PEMBANGUNAN IBU KOTA NUSANTARA - Nur Azmi Azis; Sekar Dwiyanti; Millatus Shohihah; Ahla Nurus Saada (Penerbit Universitas Atma Jaya Yogyakarta, 2026)
The development of the Nusantara Capital City (IKN) in East Kalimantan, mandated by Law Number 3 of 2022, is a strategic national project to establish a smart, sustainable, and inclusive city as Indonesia’s new administrative and economic hub. The IKN Authority, a ministerial-level body, was established to manage the development with extensive powers, including forging international cooperation for funding, technology transfer, and infrastructure development. However, these powers are constrained by Law Number 37 of 1999 on Foreign Relations, which requires coordination with the central government. This study examines the IKN Authority’s powers in entering international agreements to support IKN development and how national regulations govern these powers. Employing a normative legal approach, the study analyzes legislation, official documents, and academic literature to identify the scope of the IKN Authority’s powers and its coordination mechanisms with the central government. The findings reveal that while the IKN Authority has flexibility in attracting foreign investment and forming international partnerships, it must coordinate with the Ministry of Foreign Affairs to align with national interests. This includes approval and oversight procedures, which may impact the efficiency of international cooperation.